The Impact of Relationships, Leadership and Innovation on Organisations - Rzepka, Agnieszka (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
In the current turbulent and competitive environment, organizations continually strive to enhance their market position through inter-organizational relationships. Today, in an organization innovation plays a key role in the process of building an effective operating model. On the other hand, developing interpersonal relationships, and leadership behavior is desirable in response to the increasing demands of a turbulent environment. The author researched a sample of 622 business sector managers. The tools used were a questionnaire survey and a diagnostic survey, and, as a result, structural models were used. As a result, it was found that the type of relationship between members of an organization, the type of leadership, and innovation are correlated. The analysis shows that innovative behavior is better solved in organizations with strong leadership and, on the other hand, leaders' flexibility affects their relationships. It appears that there is relatively little research on how interpersonal relationships affect the generation and diffusion of new solutions. In this context, the results discussed and the conclusions drawn from them can be seen as an addition to the existing body of work, which should be further extended.